Nutrition status and quantification of blood minerals by TXRF spectroscopy in vegetarian and non-vegetarian university students - Alexandra Vieira Gonçalves; Rafaela Corrêa Pereira; Marcos Coelho Bissoli; Ananda Lima Sanson; Robson José de Cássia Franco Afonso; Michel Cardoso de Angelis-Pereira (Universidade Estadual de Maringá, 2019)
This study investigated whether university students following a vegetarian diet differed from non-vegetarian students in nutrient intake, biochemical, hematological and blood mineral profile of nutritionally relevant elements. In total, 107 students from a university, following either a non-vegetarian or a vegetarian diet for at least 1 year prior to the study, were recruited in two stages, setting up two experiments. Nutrient intake (experiment 1, n = 58), and biochemical and hematological parameters (experiment 2, n = 49) were evaluated. TXRF spectroscopy was used for determination of trace elements in whole blood. Vegetarians showed differences in nutrient intake, mainly higher consumption of unsaturated fatty acids and fiber. No significant differences in the biochemical and hematological parameters were found. The prevalence of abnormal parameters in a considerable number of vegetarians and non-vegetarians were found, mainly regarding high density lipoprotein (HDL-c) and total cholesterol (TC). TXRF spectroscopy proved to be a simple tool for determining nutrition-relevant elements (K, Fe, Cu and Zn) in blood samples. The high incidence of abnormal parameters, regardless of the dietary pattern, raises concern about the high prevalence of bad eating habits among young university students. Particularly for the vegetarian students, these results may partly counteract the beneficial lifestyle of a vegetarian diet evidenced by previous studies. It is important for students to be aware of its potential nutritional limitations. In this context, food and nutrition education programs in the academic context could contribute to set up autonomous and healthy subjects, regardless of the diet chosen.